THE GREAT GAME IN THE EURASIAN HEARTLAND: NEW SPIRAL - MAKHMUDOV, Rustam (CENTRAL ASIA AND THE CAUCASUS, 2009)
The collapse of the Soviet Union revived active geopolitical processes of regional and global dimensions across Central Asia. This could not but bring to mind the post-imperial past when the region was an arena for the great geopolitical game between Soviet Russia (which replaced the Russian Empire) and the British Empire. Today, the situation is much more complicated in many respects. In the early 20th century, two main players operated in a region full of weak states (Afghanistan, the Bukhara Emirate, and the like). In the early 21st century, many more outside actors are involved: Russia, the U.S. and the E.U. complete with NATO, their military component, China, Iran, Pakistan, and India. Within the region, all the local states (Uzbekistan, Kazakhstan, Turkmenistan, Kyrgyzstan, and Tajikistan) are actively positioning themselves as geopolitical entities of particular importance. Their elites have already formulated their national interests and are busy with fairly consistent strategies for their defense and promotion. The effects, however, vary depending on the countries geopolitical potential. Afghanistan is another system-forming factor of regional geopolitics that affects, if not all, at least many of their aspects. This is a unique country that geopolitically belongs to three regions—Central Asia, the Middle East, and South Asia—while remaining, to a certain extent, a sub-region with a development logic of its own.